Reflection on Practice: Designing Effective Online Discussion Forums Through the Lens of Universal Design for Learning - Jin, WanQi (Belinda); Preciado Babb, Armando Paulino (Imagining SoTL, 2026)
Asynchronous online discussion forums (AODFs) are widely used in hybrid and online post-secondary courses to promote collaborative learning and assess students’ knowledge building. This reflective essay explores how AODFs can be effectively designed and implemented as purposeful assessment tools that accommodate diverse students’ needs while enhancing the overall learning experience. Guided by the Universal Design for Learning (UDL) framework, this essay outlines strategies for creating inclusive, accessible, and engaging AODFs that promote meaningful interactions among students and between students and instructors. Drawing on current research and our reflections, the paper demonstrates how the principles of UDL—multiple means of engagement, representation, and action/expression—can transform AODFs into dynamic spaces for collaboration, reflection, and knowledge co-construction. It concludes with recommendations for aligning assessment design with learning goals and professional practice, emphasizing the importance of formative assessment, workload management, and equitable participation. This paper provides practical strategies for instructors, instructional designers, and anyone involved in developing online and blended learning environments in post-secondary education to design effective AODFs assessments that foster students’ deeper learning and meaningful interactions.